2019
DOI: 10.1002/chem.201903531
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Chain Elongation Using Unprotected Amino Acids in a Micro‐Flow Reactor

Abstract: Conventional peptide synthesis requires a deprotection step after each amidation step, which decreases synthetic efficiency. Therefore, peptide synthesis using unprotected amino acids is considered an ideal approach. Here, we report peptide chain elongation using unprotected amino acids via a mixed carbonic anhydride. Micro‐flow technology enabled rapid mixing of an organic layer containing a protected amino acid or dipeptide and an aqueous layer containing an unprotected amino acid or dipeptide to accelerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…176,177 Enabled by ow chemistry, some research groups have approached this challenge by introducing novel methods for peptide coupling. In a series of papers, 134,[178][179][180] Fuse et al have showed that by using continuous ow microreactors, strongly activated amino acids such as acid anhydrides can undergo amide coupling in seconds with efficient suppression of racemisation, due to low reaction volumes and efficient mixing. The carboxylic acids were activated to symmetrical anhydrides or mixed carbonic anhydrides in ow using solutions of triphosgene 178,179 or isobutyl chloroformate 180 in MeCN and coupled with protected or unprotected amino acids respectively (in DMF or MeCN), to afford di-, tri-and tetrapeptides in good yields (Scheme 1A).…”
Section: Peptide Synthesis In Owmentioning
confidence: 99%
“…176,177 Enabled by ow chemistry, some research groups have approached this challenge by introducing novel methods for peptide coupling. In a series of papers, 134,[178][179][180] Fuse et al have showed that by using continuous ow microreactors, strongly activated amino acids such as acid anhydrides can undergo amide coupling in seconds with efficient suppression of racemisation, due to low reaction volumes and efficient mixing. The carboxylic acids were activated to symmetrical anhydrides or mixed carbonic anhydrides in ow using solutions of triphosgene 178,179 or isobutyl chloroformate 180 in MeCN and coupled with protected or unprotected amino acids respectively (in DMF or MeCN), to afford di-, tri-and tetrapeptides in good yields (Scheme 1A).…”
Section: Peptide Synthesis In Owmentioning
confidence: 99%
“…[16] Flow chemistry thus presents itself as a rational approach to further consider in the NCA ROP-polypeptide field. [15,17,18] While recent work on continuous flow for peptide synthesis via NCA ROP has focused mainly on the formation of di-and tripeptides, [19][20][21] a flow process to synthesize NCA monomers has been recently realized by the Fuse group. [22] Challenges remain to translate the NCA ROP reaction to flow however, as so far only a few examples exist in the literature.…”
Section: Doi: 101002/marc202000071mentioning
confidence: 99%
“…Micro-ow technology enabled rapid mixing and precise control of reaction temperature (Fuse et al, 2018). Fuse et al (2019) synthesized dipeptides and tripeptides in intermediate to high yields, while the problem of puri cation process in a micro-ow reactor remained to be solved.…”
Section: Introductionmentioning
confidence: 99%